An Assessment of the Impact of Open and Distance Learning in Tertiary Institutions on Peacebuilding in Nigeria - Ibebunjo, Basil O.; Iroye, Samuel Opeyemi (West African Journal of Open and Flexible Learning, 2018)
School Curriculum is one of the most viable tools that can be used in imparting peace education in any given society and it is therefore in this regard that this study investigates the impact of Open and Distance Learning (ODL) in tertiary institutions on peace building in Nigeria. This study used the operations of the National Open University of Nigeria (NOUN) via its Study Centres model as a benchmark for the presentation and establishment of its objectives. The study aimed at examining the effect of School Curriculum at the higher institution level, most especially the Open and Distance Learning system in projecting peace building in Nigeria. Mixed method research techniques were employed to generate data from both primary and secondary sources. Analyses of results from Likert Rating Scale and interviews showed that students, teachers and staff of NOUN have a better appreciation of the ideals of peace education. Results also show that NOUN’s curriculum possesses national character which provides better ODL environment for the impartation of peace education in Nigeria. The study recommends that there should be a national regulation of tertiary peace education curricula to ensure that regular Universities key into the ideals of peace education which will help in enhancing and promoting peaceful atmosphere and co-existence in Nigeria. Résumé : Le programme scolaire est l'un des outils les plus viables qui peuvent être utilisés pour transmettre une éducation de paix à une société donnée et c'est donc à cet égard que cette étude étudie l'impact de la formation ouverte à distance (ODL) dans les établissements tertiaires sur la consolidation de la paix au Nigeria. Cette étude a utilisé les opérations de l'Université nationale ouverte du Nigeria (NOUN) par l'intermédiaire de ses centres d'études comme point de référence pour la présentation et l'établissement de ses objectifs. L'étude a examiné l'effet du programme scolaire au niveau des établissements supérieurs, en particulier le système de formation à distance dans la projection de la consolidation de la paix au Nigéria. Des techniques de recherche sur les méthodes mixtes ont été utilisées pour générer des données provenant de sources primaires et secondaires. Les analyses des résultats de l'échelle de notation de Likert et les entrevues ont montré que les étudiants, les enseignants et le personnel de NOUN ont une meilleure appréciation des idéaux de l'éducation à la paix. Les résultats montrent également que le programme d'études de NOUN possède un caractère national qui offre un meilleur environnement ODL pour l'éducation de la paix au Nigéria. L'étude recommande qu'il y ait une réglementation nationale des programmes d'enseignement supérieur sur la paix afin de s'assurer que les universités régulières intègrent les idéaux de l'éducation de la paix qui contribueront à renforcer et à promouvoir l'atmosphère et la coexistence pacifiques Nigeria.